How to Optimize Tuberculosis Health Education in College Under the New Situation? Based on a Cross-Sectional Study Among Freshmen of a Medical College in Guangxi, China - Wu, Tengyan; He, Huimin; Wei, Suosu; Pan, Jian; Yang, Jingjuan; Huang, Shi; Gan, Shijie; Ye, Chengpeng; Huo, Haiying; Tang, Zhong; Feng, Qiming (Frontiers in Public Health, 2022)
Methods A cross-sectional study was conducted among freshmen of a medical college in Guangxi, China. A self-designed questionnaire was used to conduct an on-site questionnaire survey. The data was entered in Epidata 4.4.2.1 and analysed using SPSS version 25.0. Including descriptive statistics and T test, and the criterion for statistically significant difference was P<0.05. Results A total of 583freshmen responded to the survey questionnaires. In the cognition about the 5 related knowledge of TB, it shows that 551(94.5%) freshmen knew about the predilection site of TB; 333 (57.1%), 328 (56.4%), 257 (44.1%), 201 (34.5%) freshmen knew about the pathogen, the policies about free treatment, the designated hospitals and the World TB Day. In the cognition about the 8 core knowledge of TB, the overall awareness rate among the freshmen is 73.3%(3420/4664); the awareness rate of the knowledge that “guarantee adequate sleep, reasonable diet and strengthen physical exercise can reduce the incidence of TB” among them was the highest, at 88.7%(517/583); the awareness rate of the knowledge that "coughing or sputum expectoration occurred for more than 2 weeks should be suspected of infecting TB and seeking medical treatment in time" among them was the lowest, at 47.5%(277/583). Whether you have received health education on TB (T=4.267, P=0.000) and whether you have heard of TB (T=3.739, P=0.000) are the factors. 562( 96.4%) and 565(96.9% )freshmen are willing to learn and tell others about the knowledge of TB. 370(63.5%.) freshmen willing to accept TB health education forms of “website, Weibo, and WeChat”, which is the highest. Conclusion The cognition about the 5 related knowledge of TB among freshmen is unbalanced, and the overall awareness rate of the 8 core knowledge of TB among freshmen still needs to be improved. Freshmen who have not heard of TB and have not received TB health education before enrollment are the key intervention groups. It is recommended that to make full use of modern multimedia technology, to continuously optimize the health education forms, to implement precise policies, and to strengthen the theoretical and practical health education on TB from the beginning of the freshmen entering colleges.